Metacognition analysis of five grade students in elementary school on numbers - Dyah Triwahyuningtyas; Nyamik Rahayu Sesanti (Institute of Advanced Engineering and Science, 2023)
This study aimed to observe student learning activities in terms of number material metacognition. The method is a case study qualitative research. The research subjects were 30 students of the fifth-grade elementary school in Malang. Data collection techniques use tests and interviews by carrying out three stages: planning, monitoring, and evaluation. The results showed that internal and external factors caused 75% of moderate learning difficulties. Internal factors arise due to a lack of understanding of mathematical concepts, lack of thoroughness, and interest in literacy. Meanwhile, the external media used by the teacher was deemed less supportive, and the class conditions were not conducive. Thus, there is a conclusion that internal and external factors cause students’ metacognition analysis.